2014
DOI: 10.4028/www.scientific.net/amm.602-605.3144
|View full text |Cite
|
Sign up to set email alerts
|

Research on Longitudinal Aerodynamics Modeling Method for Aircraft Stall Based on Wavelet Neural Network from Flight Data

Abstract: For the aerodynamic modeling problem from measured flight data for aircraft stall, a WNN aerodynamic modeling method is proposed. According to the aerodynamic modeling flow from flight data for aircraft stall, WNN is introduced to establish the aerodynamic model of aircraft for stall phenomenon. Experiment shows that the method can improve the modeling ability of WNN, and is suitable for actual aerodynamic modeling for aircraft stall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…With establishing a connection between the nonlinear behaviors and system status parameters, the prediction on the occurrence of the rotating stall in the compressor has been carried out in practical application. An aerodynamic modeling for an aircraft stall was proposed by Gan [ 12 ] with the wavelet neural network (WNN). The results showed that this method could improve the modeling ability of the WNN, which was suitable for the aerodynamic modeling of the stall flow.…”
Section: Introductionmentioning
confidence: 99%
“…With establishing a connection between the nonlinear behaviors and system status parameters, the prediction on the occurrence of the rotating stall in the compressor has been carried out in practical application. An aerodynamic modeling for an aircraft stall was proposed by Gan [ 12 ] with the wavelet neural network (WNN). The results showed that this method could improve the modeling ability of the WNN, which was suitable for the aerodynamic modeling of the stall flow.…”
Section: Introductionmentioning
confidence: 99%